(untitled) (Canadian Perspectives on Academic Integrity, 2020)
Purpose: The purpose of this article is to share details of the methodological decisions regarding data collection that a researcher or research team may want to consider when undertaking a policy analysis. Methods: We have undertaken a meticulous documentation of our decision-making processes throughout the research design process. Results: We provide narrative evidence of what worked for us as a collaborative research team. Implications: Understanding the decisions we made throughout our research design and implementation may help other research teams, particularly those working as virtual collaborations and/or those undertaking academic integrity policy analysis.